Image‐guided percutaneous renal cryoablation: preoperative risk factors for recurrence and complications - Blute, Jr, Michael L.; Okhunov, Zhamshid; Moreira, Daniel M.; George, Arvin K.; Sunday, Suzanne; Lobko, Igor I.; Vira, Manish A. (BJU international, 2013)
What's known on the subject? and What does the study add? Given that percutaneous cryoablation (PCA) is a relatively new procedure, there are few studies published on this treatment with almost no long‐term follow‐up. The percutaneous approach, while not the first choice treatment for RCC, may be most appropriate for older patients with several comorbidities as it offers less invasive outpatient management of small renal masses (SRMs). It is therefore important to measure procedural outcomes noting rates of complications and reasons for treatment failure or recurrence. To our knowledge, this is the first paper applying the R.E.N.A.L nephrometry scoring system to PCA of SRMs. The study adds insight into procedural outcomes from this treatment. Little has been published on this treatment strategy, but it has been increasingly considered for patients who are not candidates for traditional surgical approach. It is important to study and establish the outcomes of all treatments used by physicians. It is also necessary to understand treatment complications – how and why they occur – and seek reasons for treatment failure and recurrence. This allows physicians to choose the best management for each individual patient to improve outcomes. OBJECTIVE • To investigate the value of the R.E.N.A.L nephrometry scoring system in predicting treatment success for image‐guided percutaneous cryoablation (PCA). PATIENTS AND METHODS • The study included 139 patients with renal masses treated with PCA. • Preoperative computed tomography or magnetic resonance images were reviewed by a urology resident. • The primary endpoint variable was incomplete treatment or tumour recurrence. • R.E.N.A.L. scores were categorized into low (4–6), moderate (7–9), and high (10–12). • Logistic regression analysis was conducted to predict tumour recurrence. Additional variables collected included age at surgery, American Society of Anesthesiologists score, lesion size, skin‐to‐tumour distance, skin‐to‐hilum distance, and number of treatment cryoprobes. RESULTS • At a median follow‐up of 24 months, there were 10 tumour recurrences (six moderate and four high R.E.N.A.L. score categories). Nephrometry score and number of probes used were not associated with recurrence (odds ratio [OR] 1.02, P= 0.9 and P= 0.53, respectively). • The tumour distances for patients with recurrence and no recurrence were 10.8 cm and 8.5 cm, respectively (P≤ 0.05), the skin‐to‐tumour distance was associated with treatment failure (OR 1.24, P= 0.015); for each unit increase in the mean value, patients were 1.5 times more likely to have a tumour recurrence (95% confidence interval [CI] 1.04–1.72). • The model that best predicted complications included the number of probes used (P= 0.002) and R.E.N.A.L. score (OR 1.35, P= 0.027). For each additional probe used, patients were twice as likely to have complications (OR 1.98, 95% CI 1.28–3.05). With each unit increase in R.E.N.A.L. score, patients were 1.5 times more likely to experience a complication (OR 1.49, 95% CI 1.05–2.11). CONCLUSIONS • An increased skin‐to‐tumour distance is associated with a higher risk of treatment failure after PCA. • Furthermore, an increase in both R.E.N.A.L nephrometry score and number of probes used was associated with an increased risk of complications after PCA. • The R.E.N.A.L. nephrometry score as a measure of tumour complexity was not associated with tumour recurrence.